Perencanaan Sarana Prasarana dan Perannya dalam Meningkatkan Mutu Pendidikan - Donumo, Musdahlifa; Lestari, Dwi Indah (CV. Kurnia Grup, 2024)
Discussion related to planning and management of educational facilities and infrastructure and their role in improving the quality of education. Some of the main issues raised include the concept of planning facilities and infrastructure, the contribution of facilities and infrastructure management to improving the quality of education, as well as challenges and solutions in planning and managing educational facilities and infrastructure itself. Regarding the planning concept, this discussion emphasizes the importance of considering various aspects, such as needs analysis, procurement, inventory, maintenance and write-off. Good management can make a significant contribution to improving the quality of education. This can be achieved through the provision of adequate learning facilities, regular care and maintenance, and effective utilization. However, this discussion will also identify several challenges faced, such as budget limitations, inadequate maintenance, and suboptimal coordination. To overcome these challenges, this document suggests the need for commitment and responsibility from the school, especially the school principal, as well as good coordination with relevant stakeholders. Therefore, good planning and management of facilities and infrastructure is very important to improve the quality of education. However, there are several challenges that need to be overcome through collaborative efforts between schools and stakeholders. So that the Institution can ensure optimal availability, maintenance and utilization of educational facilities and infrastructure to support improving the quality of education.